Формування Soft Skills у співробітників у сфері надання послуг - Пелех, Олена Ігорівна; Pelekh, Olena Ihorivna (Ірпінь, 2023)
У кваліфікаційній роботі теоретично обґрунтовано і розкрито формування навиків «Soft skills» під час робочого процесу у товаристві, що ґрунтується на робочому принципі «людина-людина». Предметом дослідження були соціальні умови формування «soft skills» у працівників товариства. Описано розроблене тренінгове заняття, яке можна використати у роботі з працівниками бізнес сфери для формування у них навичок «soft skills».

In the qualification work, the formation of "Soft skills" during the work process in the company based on the working principle of "person-person" is theoretically substantiated and disclosed. The subject of the study was the social conditions for the formation of "soft skills" among company employees. The developed training course is described, which can be used in work with employees of the business sphere for the formation of "soft skills" in them.
Formation of Soft Skills among employees in the field of service provision
Keywords: емоційний інтелект; комунікативні навички; м’які навички; «Soft skills»; emotional intelligence; communication skills